GFU Species Brochures - Global Facilitation Unit for Underutilized Species (2007)
The GFU, in an effort to increase awareness and understanding of the potential underutilized species hold for improvement of livelihoods, has gathered commercial samples of products coming from these species that belong to an exhibit showcase whenever possible and appropriate. The links point to brochures that have been developed for each of the underutilized species that features the items on display and have the prime objective to help in getting the message across; income generation is a reality if an appropriate plan and marketing strategy is pursued. The following GFU species brochures are available Abaca - Musa textilis Amaranth - Amaranthus spp Amazonia species - Euterpe oleracea - Myrciaria dubia - Eugenia stipitata Andean potatoes - Solanum tuberosumCanihua - Chenopodium pallidicaule Emmer - Triticum dicoccum Henna - Lawsonia inermis Laurel - Laurus nobilis Makoni - Fadogia ancylantha Marula - Sclerocarya birrea Masau - Ziziphus mauritiana Maya Nut - Brosimum alicastrumMinor Millets - Eleusine coracana - Setaria italica - Paspalum scrobiculatum - Panicum miliaceum - Panicum sumatrense - Digitaria exilis Moringa - Moringa oleifera Noni - Morinda citrifolia Oca - Oxalis tuberosa Physic Nut - Jatropha curcas Quinoa - Chenopodium quinoa Seabuckthorn - Hippophae rhamnoides